Guild boss [large type] - Castle, Jayne (Thorndike Press large print core series., 2022)
"Kidnapped and drugged, Lucy Bell manages to escape--only to find herself lost in the maze of tunnels beneath Illusion Town. Gabriel Jones is the Ghost Hunter sent to rescue her. With no rational reason for her abduction, and her sole witness gone on another assignment for the Guild, whispers start circulating that Lucy made it all up. But a killer is still hunting her, and there aren't a lot of options when it comes to heroes. Despite her wariness, Gabriel is the one person who believes Lucy. He's determined to help clear her reputation. And as the new Guild Boss, his word is law, even in the lawlessness of Illusion Town."--Back cover.